The Emergence of Islamic Theological Issues: Khawarij and Murji'ah - A. Ghaza Muh. Albar; Nurlaelah Abbas; Mahmuddin Mahmuddin (Penerbit Hellow Pustaka, 2026)
This research provides the emergence of early Islamic theological issues by focusing on two major sects, namely the Khawarij and the Murji’ah. The study aims to explain the historical background of the emergence of these two sects, their theological doctrines, and their influence on the development of Islamic thought. This research employs a qualitative method with a literature review approach, analyzing both classical and contemporary sources. The findings indicate that the Khawarij developed a strict and exclusive theology, including the practice of takfīr toward perpetrators of major sins, while the Murji’ah emerged as a moderate response by postponing judgment of faith to Allah (Swt.). Both sects made significant contributions to the discourse of Islamic theology.